Market Integration Assessment a Block Chain of Technologies in Regional Economic Systems in Comparison to the Global Supply Chain Management (On the Example of Regions of the Volga Federal District) - Marat Rashitovich Safiullin; Leonid Alekseevich Elshin; Kurbangalieva Dinara Lenarovna (International Journal of Supply Chain Management, 2019)
The article discloses methodological approaches to quantifying the level of penetration of block chain technologies into the regional socio-economic environment in comparison to the supply chain strategies. Based on the methods of mathematical and statistical analysis, it allows you to formalize and convert a large array of data of a qualitative order into a single scale for measuring the process under study - the level of demand in the regional socio-economic environment for block chain technology. The developed methodology is based on the theory of reputational economics, which allows, based on a system analysis of the global information space, to identify the level of demand for the research object in regional markets. Based on the collected and processed array of information and statistical data, the work carried out estimates of the index of reputation capital in the field of block chain technologies in the regions of the Volga Federal District for the period from 2010 to 2018. Based on the presented calculation data, a scientifically-based conclusion was obtained, according to which the regional â€œblock chainâ€ processes are beginning to take over the regional space of Russia more and more every year. Moreover, undoubtedly, as well as for any other phenomenon, this process is very differentiated in terms of penetration into the regional environment. In accordance with the estimates obtained, the regions with the highest level of demand for block chain technology and the outsider regions were identified. The implemented algorithm for the formalized assessment of the penetration of distributed data storage technologies into the regional environment creates the basis for a comparative analysis of the development efficiency of regions, determining their current and future competitiveness in the context of globalization and digitalization of reproduction processes.